Home » Blog » Prove that sums of trig functions can be expressed as sums of complex exponentials

Prove that sums of trig functions can be expressed as sums of complex exponentials

Prove that sums of the form

    \[ S_n (x) = \frac{1}{2}a_0 + \sum_{k=1}^n (a_k \cos (kx) + b_k \sin (kx)) \]

are equal to sums of the form

    \[ S_n (x) = \sum_{k=-n}^n c_k e^{ikx}. \]


Proof. We compute this directly, substituting in the formulas for sine and cosine in terms of the complex exponential,

    \[ \sin (kx) = \frac{e^{ikx} - e^{-ikx}}{2i}, \quad \text{and} \quad \cos (kx) = \frac{e^{ikx} + e^{-ikx}}{2}, \]

that we derived in this exercise. So, we have

    \begin{align*}  S_n (x) &= \frac{1}{2}a_0 + \sum_{k=1}^n (a_k \cos (kx) + b_k \sin (kx)) \\[9pt]  &= \frac{1}{2}a_0 + \sum_{k=1}^n \left( a_k \frac{e^{ikx} + e^{-ikx}}{2} + b_k \frac{e^{ikx} - e^{-ikx}}{2i} \right) \\[9pt]  &= \frac{1}{2}a_0 + \frac{1}{2} \sum_{k=1}^n \left( a_k e^{ikx} + a_k e^{-ikx} - ib_k e^{ikx} + i b_k e^{-ikx} \right) \\[9pt]  &= \frac{1}{2} a_0 + \frac{1}{2} \sum_{k=1}^n \left( a_k - ib_k\right)e^{ikx} + \frac{1}{2} \sum_{k=1}^n \left( a_k + ib_k \right)e^{-ikx} \\[9pt]  &= \frac{1}{2}a_0 + \frac{1}{2} \sum_{k=1}^n (a_k - i b_k )e^{ikx} + \frac{1}{2} \sum_{k=-n}^{-1} (a_{-k} + ib_{-k})e^{ikx} \\[9pt]  &= \frac{1}{2} a_0 + \frac{1}{2} \sum_{k=1}^n c_k e^{ikx} + \frac{1}{2} \sum_{k=-n}^{-1} c_{-k}e^{ikx} \\[9pt]  &= \sum_{k=-n}^n c_k e^{ikx} \end{align*}

where

    \[c_k = \frac{1}{2} (a_k - ib_k), \quad c_{-k} = \frac{1}{2}(a_{-k} + ib_{-k}), \quad c_0 = 0. \qquad \blacksquare \]

Point out an error, ask a question, offer an alternative solution (to use Latex type [latexpage] at the top of your comment):